2021
DOI: 10.3390/ijms22115549
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Animal Models: Elucidation of Biomarkers and Therapeutic Approaches for Cognitive Impairment

Abstract: Alzheimer’s disease (AD) is an age-related and progressive neurodegenerative disorder. It is widely accepted that AD is mainly caused by the accumulation of extracellular amyloid β (Aβ) and intracellular neurofibrillary tau tangles. Aβ begins to accumulate years before the onset of cognitive impairment, suggesting that the benefit of currently available interventions would be greater if they were initiated in the early phases of AD. To understand the mechanisms of AD pathogenesis, various transgenic mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 222 publications
(250 reference statements)
0
19
0
5
Order By: Relevance
“…For the purpose of designing therapeutics or disease modifying agents for AD treatment, a wide variety of animal models have been developed to replicate the human environment of the disease [ 70 , 71 , 72 , 73 , 74 ]. In particular, the first aim of most AD animal models is to develop the neuropathological features that precede the cognitive dysfunction [ 75 , 76 , 77 ].…”
Section: Metformin As An Antidiabetic Drug Strategy For Alzheimer’s Disease Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of designing therapeutics or disease modifying agents for AD treatment, a wide variety of animal models have been developed to replicate the human environment of the disease [ 70 , 71 , 72 , 73 , 74 ]. In particular, the first aim of most AD animal models is to develop the neuropathological features that precede the cognitive dysfunction [ 75 , 76 , 77 ].…”
Section: Metformin As An Antidiabetic Drug Strategy For Alzheimer’s Disease Treatmentmentioning
confidence: 99%
“…These models do not display all the anomalies found in human AD and do not duplicate the sporadic forms of AD, because they only reproduce the pathological features of AD common mutated genes [ 77 ]. However, transgenic innovation gives special opportunity to replicate the cause of familial AD by transfecting a mutant human APP [ 74 , 75 ]. Mice models enabled our understanding of Aβ-production, deposition, and clearance-related molecular pathways and the impact of Aβ on the neuronal network and synapses [ 73 , 74 ].…”
Section: Metformin As An Antidiabetic Drug Strategy For Alzheimer’s Disease Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…After polymerization, the Aβ oligomeric structures devolve into a hazardous molecule, which activates microglia and produces reactive oxygen species (ROS) and inflammatory cytokines, resulting in severe neuronal injury [53,54]. Various amyloid cascade hypothesis-related AD animal models have been developed over the years in order to identify novel therapeutic medications for AD therapy [55,56]. Indeed, it has been shown that the intracerebral administrations of Aβ induces neurodegeneration, as well as deficiencies in learning and memory [55,57].…”
Section: Admentioning
confidence: 99%
“…However, it must be acknowledged that these models are not totally faithful copies of the cognitive changes encountered in patients with AD, as they can only partially replicate the anatomopathological changes [ 53 ]. Thus, the different murine models (double-transgenic [ 54 ] and triple-transgenic [ 55 ] AD mouse model) replicate the appearance of senile plaques formed by amyloid beta and hyperphosphorylated tau neurofibrils, the main characteristics of AD neurodegeneration, but with the abovementioned limitations.…”
Section: Caffeine and The Correlation With Alzheimer’s Diseasementioning
confidence: 99%